College Students' Cognitive Learning Outcomes in Technology-Enabled Active Learning Environments: A Meta-Analysis of the Empirical Literature. (July 2020) - Shi, Yinghui; Yang, Huiyun; MacLeod, Jason; Zhang, Jingman; Yang, Harrison Hao
Technology-enabled active learning environments (TE-ALEs) have attracted considerable research interest, particularly in higher education. However, research shows inconsistent results describing the influence of TE-ALEs toward students' cognitive learning outcomes. This study was designed to identify high-quality empirical research examining college students' cognitive learning outcomes and to utilize meta-analysis to determine the overall effectiveness of TE-ALEs. A systematic literature search identified 31 high-quality peer-reviewed journal articles that met the inclusion criteria. Meta-analysis showed that the calculated effect size of TE-ALEs more positively influenced students' cognitive learning than traditional lecture-based environments. Moderator variable analysis suggested that social context, study design, and sample size were significant factors that influence the effectiveness of TE-ALE. TE-ALEs were found more effective when instructors employed individualized learning contexts as well as when bias was reduced in randomized controlled trials. TE-ALEs were also found to be more effective in small courses rather than in large courses.